Autonomic nervous system evaluation in Type 2 diabetic patients and effect of its duration - Karki, DB; Acharya, S; Shrestha, P; Pant, S; Pokhrel, A; Bista, P (Journal of Kathmandu Medical College, 2013)
Introduction: Dysfunction of the autonomic nervous system is common in diabetic patients. Presence of autonomic dysfunction should alert the physicians of its serious consequences that require timely preventive measures. Objectives: This study was done to fi nd out the autonomic nervous system involvement in Type 2 diabetic patients and to see its relation with the duration of diabetes. Methods: This was a hospital based cross-sectional study. All consecutive diabetic patients of both genders attending Kathmandu Medical College and a private clinic, Temple of Healing were included. A battery of six well validated and accepted autonomic nervous system evaluation tests were done to evaluate the autonomic function in 245 Type 2 diabetic patients. Results: Prevalence of autonomic dysfunction was found to be 71.02% with 58.78% patients having mild autonomic dysfunction and 12.24% having moderate dysfunction. Severe autonomic dysfunction was detected in none of the patients. Parasympathetic dysfunction was much more common than sympathetic dysfunction (68.16% vs. 17.96%). No association was found between autonomic dysfunction and duration of diabetes. Conclusions: Autonomic dysfunction is very common in diabetics and can be detected by simple tests. Timely detection of autonomic dysfunction in diabetic patients is advised so that its preventive measures can be effective. DOI: http://dx.doi.org/10.3126/jkmc.v1i2.8142 Journal of Kathmandu Medical College, Vol. 1, No. 2, Oct.-Dec., 2012: 77-83